Green synthesis of graphene quantum dots from rice flour - Tran, Quyen, Thi Bich; Huynh, Phuong Thi Thuy; Ngo, My, Nguyen Tra; Doan, Thien, Van Hong; Luong, Thanh, Huynh Vu; Tran, Lan, Nguyen Phuong (Vietnam Journal of Science and Technology, 2023)
Graphene Quantum Dots (GQDs) were successfully synthesized by a green and eco-friendly synthetic method using abundant and naturally available raw materials from rice flour. This study suggested and compared two aggressive approaches to fabricate GQDs, which are hydrothermal method at 170 °C for 8 h and microwave irradiation method at 900 W with a short reaction time of 30 min. The results showed that the hydrothermal method produced GQDs with better nanoparticle size and properties than the microwave irradiation method. Furthermore, the products were only GQDs, water and carbide precipitate, thus avoiding complicated post-processing steps. The synthesized GQDs were determined for their morphology by Transmission electron microscope (TEM) showing spherical nanoparticles with an average size of 5-7 nm and 10-14 nm for hydrothermal and microwave irradiation methods, respectively. Besides, these GQDs were also analyzed for their characterizations, morphologies and compositions by UV-vis, XRD and FTIR. Thanks to their low cytotoxicity, good optical stability, and excellent photo-luminescence property, GQDs have become novel nanostructured materials in many application fields from energy to biomedicine and environment such as sensors, bio-imaging, drug carriers, and solar cells.